Corporate events - Syrkina, A. Yu. (ТДАТУ, 2021)
Сorporate events are an effective way for companies to engage with customers or employees. Any business that wants to build lasting relationships holds affairs of this kind. Hosting a corporate affair allows to enhance bonds with current clients and partners, and attract future ones.
Keywords: organization of corporate events; message